Comprehensive landscape and interference of clonal haematopoiesis mutations for liquid biopsy: A Chinese pan‐cancer cohort. Issue 21 (17th October 2021) - Xu, Enwu; Su, Kai; Zhou, Yang; Gong, Longlong; Xuan, Yiwen; Liao, Ming; Cao, Jiawang; Li, Yaqian; Lu, Yujiao; Zhao, Yi; Chen, Fengxia
Abstract: Tumour‐derived DNA found in the plasma of cancer patients provides the probability to detect somatic mutations from circulating cell‐free DNA (cfDNA) in plasma samples. However, clonal hematopoiesis (CH) mutations affect the accuracy of liquid biopsy for cancer diagnosis and treatment. Here, we integrated landscape of CH mutations in 11, 725 pan‐cancer patients of Chinese and explored effects of CH on liquid biopsies in real‐world. We first identified 5933 CHs based on panel sequencing of matched DNA of white blood cell and cfDNA on 301 genes for 5100 patients, in which CH number of patients had positive correlation with their diagnosis age. We observed that canonical genes related to CH, including DNMT3A, TET2, ASXL1, TP53, ATM, CHEK2 and SF3B1, were dominant in the Chinese cohort and 13.29% of CH mutations only appeared in the Chinese cohort compared with the Western cohort. Analysis of CH gene distribution bias indicated that CH tended to appear in genes with functions of tyrosine kinase regulation, PI3K‐Akt signalling and TP53 activity, suggesting unfavourable effects of CH mutations in cancer patients. We further confirmed effect of driver genes carried by CH on somatic mutations in liquid biopsy of cancer patients. Forty‐eight actionable somatic mutations in 17 driver genes were considered CH genes in 92 patients (1.80%) of the Chinese cohort, implying potential impacts of CH on clinical decision‐making. Taken together, this study exhibits strong evidence that gene mutations from CH interfere accuracy of liquid biopsies using cfDNA in cancer diagnosis and treatment in real‐world.